SMUTTY FANTASY IN THE DIGITAL SPHERE: SELF-PUBLISHED EROTIC ROMANCE AND SPACES OF ALTERNATIVE FEMININISM - Gilbert, Anne (AoIR Selected Papers of Internet Research, 2015)
Feminist perspectives on the romance novel are often ambivalent as they attempt to reconcile its contradictions: On one hand is the liberatory possibility of sexually explicit fantasies authored by and for women, but this is countered by the reality of a genre that frequently reverts to safe, accepted reinscriptions of heteronormative values. In this presentation, I consider how these tensions play out in a digital sphere, where the rise of e-books and digital publishing platforms has created a market for independent romance authors, erotic self-published novels, and networks of blogs and recommendation sites supporting them. I argue that the cottage industry of erotic romance e-books and review blogs represent an online space of gendered conversation, an opportunity for participants to legitimate devalued, feminized, risqué texts, as well as the practices of both writing and reading them.